Proof: Get Begin Expr Params 13
Let's prove the following theorem:
if the following are true:
- expression state at time 13 = "begin_expr"
- the expression at time 13 =
__eq__(7, 9)
- arguments stack at time 13 = [ ]
then arguments stack at time 14 = [ [ 7, [ 9, [ ] ] ], [ ] ]
Proof:
Given
1 | expression state at time 13 = "begin_expr" |
---|---|
2 | the expression at time 13 = __eq__(7, 9) |
3 | arguments stack at time 13 = [ ] |
# | Claim | Reason |
---|---|---|
1 | arguments stack at time (13 + 1) = [ [ 7, [ 9, [ ] ] ], arguments stack at time 13 ] | if expression state at time 13 = "begin_expr" and the expression at time 13 = __eq__(7, 9) , then arguments stack at time (13 + 1) = [ [ 7, [ 9, [ ] ] ], arguments stack at time 13 ] |
2 | [ [ 7, [ 9, [ ] ] ], arguments stack at time 13 ] = [ [ 7, [ 9, [ ] ] ], [ ] ] | if arguments stack at time 13 = [ ], then [ [ 7, [ 9, [ ] ] ], arguments stack at time 13 ] = [ [ 7, [ 9, [ ] ] ], [ ] ] |
3 | arguments stack at time (13 + 1) = [ [ 7, [ 9, [ ] ] ], [ ] ] | if arguments stack at time (13 + 1) = [ [ 7, [ 9, [ ] ] ], arguments stack at time 13 ] and [ [ 7, [ 9, [ ] ] ], arguments stack at time 13 ] = [ [ 7, [ 9, [ ] ] ], [ ] ], then arguments stack at time (13 + 1) = [ [ 7, [ 9, [ ] ] ], [ ] ] |
4 | 13 + 1 = 14 | 13 + 1 = 14 |
5 | arguments stack at time (13 + 1) = arguments stack at time 14 | if 13 + 1 = 14, then arguments stack at time (13 + 1) = arguments stack at time 14 |
6 | arguments stack at time 14 = [ [ 7, [ 9, [ ] ] ], [ ] ] | if arguments stack at time (13 + 1) = arguments stack at time 14 and arguments stack at time (13 + 1) = [ [ 7, [ 9, [ ] ] ], [ ] ], then arguments stack at time 14 = [ [ 7, [ 9, [ ] ] ], [ ] ] |
Comments
Please log in to add comments